Systematic Review on Hierarchical Culture and Symbolic Violence in Medical Education Environment - Posangi, Iddo (CV. Publikasi Indonesia, 2025)
The medical education environment is often characterized by a strong hierarchical culture, where power imbalances have the potential to give rise to various forms of symbolic violence that are difficult to detect directly. Symbolic violence within medical education systems can negatively impact the psychological well-being of students and medical staff, as well as disrupt the learning process and professionalism within the institution. The aim of this study is to comprehensively review existing literature regarding the role of hierarchical culture in creating and sustaining symbolic violence in medical education environments, as well as to identify its effects on the well-being and professional development of learners, in order to formulate strategic recommendations for more equitable and supportive structural changes. This study uses the Systematic Literature Review (SLR) method to examine in depth the culture of hierarchy and symbolic violence in medical education. SLR was conducted systematically and transparently to identify, assess and synthesize relevant scientific evidence, while assessing the quality of the findings to gain a comprehensive understanding. Data were collected through documentation techniques on scientific literature and documents, enabling the identification of historical and contextual patterns of symbolic violence. The results of the systematic review indicate that the entrenched hierarchical culture in medical education often triggers subtle yet significant symbolic violence. This symbolic violence emerges through hidden mechanisms of domination, such as language, attitudes, and social norms that position certain parties as morally, ethically, and professionally superior. The most commonly reported negative impacts include psychological pressure, decreased motivation to learn, and the creation of an academic environment that is unconducive to the development of competencies and the well-being of medical students.